Assessment tool for nursing student computer competencies. - Elder BL; Koehn ML (Nursing Education Perspectives (National League for Nursing), 2009)
Computer skills have been established as important for nursing students and for graduate nurses. No current research was found on the best method to evaluate the skills of incoming nursing students. The purpose of this descriptive, correlational study was to compare student ratings of their computer competency to their performance of those skills on a computer-graded assessment. A convenience sample of 87 nursing students was used. There was a low, but significant correlation between the scores on the survey and the assessment. The results suggest that students rate themselves higher on their skills than their actual performance of computer skills. Implications for educators are presented, and the value of using a computer-graded assessment is discussed.